2018
DOI: 10.1139/cjpp-2017-0383
|View full text |Cite
|
Sign up to set email alerts
|

Remote myocardial injury: the protective role of fluoxetine

Abstract: Aortic cross-clamping-induced ischemia-reperfusion (IR) is an important factor in the development of postoperative acute cardiac injury following abdominal aortic surgery. We investigated the possible anti-oxidant/anti-inflammatory effects of fluoxetine (FLX), which is used widely as a preoperative anxiolytic on cardiac injury induced by IR of the infrarenal abdominal aorta. FLX was administered to IR-performed (60 min of ischemia and 120 min of reperfusion) rats for 3 days, once daily at 20 mg/kg i.p. dosage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…SSRIs may also have protective effects in developing ischemic heart disease due to their influence on platelet reactivity and inflammatory markers 12 and insulin sensitivity. Fluoxetine was shown to decrease inflammatory markers including IL-1B, IL-6, CK, CK-MB, lipid hydroperoxide, and improved antioxidant balance following aortic cross-clamping reperfusion injury in one animal study 26 , and reduced inflammation and oxidative stress in an animal model of kidney injury 27 . Paroxetine was shown to selectively inhibit G protein-coupled receptor kinase 2 (GRK2), which increases contractility in isolated cardiomyocytes and is a potential target for heart failure therapy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…SSRIs may also have protective effects in developing ischemic heart disease due to their influence on platelet reactivity and inflammatory markers 12 and insulin sensitivity. Fluoxetine was shown to decrease inflammatory markers including IL-1B, IL-6, CK, CK-MB, lipid hydroperoxide, and improved antioxidant balance following aortic cross-clamping reperfusion injury in one animal study 26 , and reduced inflammation and oxidative stress in an animal model of kidney injury 27 . Paroxetine was shown to selectively inhibit G protein-coupled receptor kinase 2 (GRK2), which increases contractility in isolated cardiomyocytes and is a potential target for heart failure therapy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a small, randomized, double-blind placebo-controlled trial, the antidepressant fluoxetine was shown to be effective in the treatment of major MDD for three months after AMI [59]. The mechanism of fluoxetine action may be antioxidant and anti-inflammatory [60]. Another randomized, double-blind, placebocontrolled study in patients with AMI found that paroxetine improves cardiac function after AMI by inhibiting G protein-coupled receptor kinase 2 (GRK2), and it is also a widely used antidepressant [61].…”
Section: Available Marketed Drugsmentioning
confidence: 99%